Luchas y Partidos Políticos en Guatemala - Guerra Vilaboy, Sergio (2014)
This paper seeks an approach to the historical facts of the bloody experiences of exploitation that has suffered the Guatemalan people, which date back to the very beginning of the Spanish conquest and its ongoing process of subjugation that led the poet Luis Cardoza back Aragon to describe their country as the Land of Eternal Tyranny. The purpose of this analysis is to broadly provide an overview of the political and social developments in Guatemala since independence to the present, with an emphasis on the transformations of Guatemala's socioeconomic structure, the action of the political parties- mostly of them of bourgeois attachment and its influence on the national situation and progress of the revolutionary struggle. Nowadays, in the 21st. century, the problems of violence, insecurity and inequality in Guatemala continue calling for a solution but now stirred by new challenges and threats that hangs over the Land of Eternal Spring.